The 8.2ka event and Early–Mid Holocene forests, fires and flooding in the Central Ebro Desert, NE Spain (Quaternary Science Reviews, 2007)
The impact of the 8.2 ka cooling event during the Early–Mid Holocene has not been widely observed in Southern Europe, which in contrast to Northern Europe, was already experiencing a cooler than present climate at this time. Multi-proxy analysis of sediment cores from two closed-basin saline lakes in the Central Ebro Desert (NE Spain) has allowed us to investigate the impact of climatic changes around the time of this event in more detail. Long-term changes in climate between the Early and Mid Holocene indicate a shift in winter to a more positive NAO, resulting in declining lake levels in one lake sensitive to winter groundwater recharge, and cooler winter temperatures reconstructed from pollen–climate analysis. Reconstructed summer temperatures also declined over this period while annual precipitation and forest cover increased, interpreted as a result of enhanced convection-driven summer precipitation association with a northward displacement of the sub-tropical high pressure. Around 8.2 ka, a marked increase in ﬁre frequency is shown between ca 8.8 and 8.0 ka BP, along with an expansion of ﬁre-tolerant evergreen oak and peak in water levels in a second storm run-off fed lake. A maximum in ﬁre intensity occurred with the deposition of a charcoal layer at both lake sites dated to 81507130 and 82857135 cal BP, respectively. The increase in ﬁre is largely attributed to a temporary return southward of the summer sub-tropical high pressure over the Mediterranean, which not only increased summer aridity, but also caused a contradictory regional warming before Hemispheric cooling set in